2021
DOI: 10.5194/amt-14-647-2021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyoxymethylene (POM-H Delrin) off-gassing within the Pandora head sensor on direct-sun and multi-axis formaldehyde column measurements in 2016–2019

Abstract: Abstract. Analysis of formaldehyde measurements by the Pandora spectrometer systems between 2016 and 2019 suggested that there was a temperature-dependent process inside the Pandora head sensor that emitted formaldehyde. Some parts in the head sensor were manufactured from the thermal plastic polyoxymethylene homopolymer (E.I. Du Pont de Nemour & Co., USA; POM-H Delrin®) and were responsible for formaldehyde production. Laboratory analysis of the four Pandora head sensors showed that internal formaldeh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…CH 2 O exhibits quite different behavior with surface values changing very little throughout the day. Despite earlier publications highlighting Pandora observations of CH 2 O ( Herman et al, 2018 ; Spinei et al, 2018 ), column observations are not shown due to the discovery of an interference ( Spinei et al, 2021 ). Nevertheless, the DC-8 profiles corroborate the stability in surface CH 2 O values.…”
Section: Role Of Satellite Observationsmentioning
confidence: 81%
See 1 more Smart Citation
“…CH 2 O exhibits quite different behavior with surface values changing very little throughout the day. Despite earlier publications highlighting Pandora observations of CH 2 O ( Herman et al, 2018 ; Spinei et al, 2018 ), column observations are not shown due to the discovery of an interference ( Spinei et al, 2021 ). Nevertheless, the DC-8 profiles corroborate the stability in surface CH 2 O values.…”
Section: Role Of Satellite Observationsmentioning
confidence: 81%
“…Given the direct emission of nitrogen oxides, NO 2 shows areas of concentration early in the day. (Herman et al, 2018;Spinei et al, 2018), column observations are not shown due to the discovery of an interference (Spinei et al, 2021 (Schroeder et al, 2017) and serve as a reminder that the integration of satellite data with multi-perspective observations and models as shown in Figure 1 is the key to providing new insight into emissions and their impacts on air quality from local to regional scales.…”
Section: Role Of Satellite Observationsmentioning
confidence: 99%
“… 82 85 We do not use HCHO columns from the Pandora spectrometers due to sensor off-gassing-induced errors in the current 2018 products. 86 Trace gas abundances along the light path are determined using differential optical absorption spectroscopy (DOAS). The estimated error in the Pandora retrievals of total VCDs of NO 2 (NO 2 -VCD Total ) is approximately 1.35 × 10 15 molecules/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“… Pandora spectrometers were deployed at 10 sites during LISTOS: Rutgers (NJ), Bayonne (NJ), Manhattan (NY), Queens College (NY), Bronx Pfizer (NY), Flax Pond (NY), Westport (CT), New Haven (CT), Hammonasset (CT), Outer Island (CT) (Figure S1a); and at three sites during the OWLETS-2 campaign: Earth System Science Interdisciplinary Center (ESSIC), the University of Maryland Baltimore County (UMBC), and Hart-Miller Island (HMI), all in Maryland (Figure S1c). , The Pandora instruments are ground-based ultraviolet–visible spectrometers that can operate in direct-sun and sky-scan mode to retrieve O 3 , NO 2 , sulfur dioxide (SO 2 ), HCHO total columns, tropospheric columns, and vertical profiles. We do not use HCHO columns from the Pandora spectrometers due to sensor off-gassing-induced errors in the current 2018 products . Trace gas abundances along the light path are determined using differential optical absorption spectroscopy (DOAS).…”
Section: Methodsmentioning
confidence: 99%
“…The ∼90 s Pandora observations (n = 4,937) were colocated with an AirKorea ozone and NO x monitor. Pandora ΩHCHO has been corrected for known a positive interference from Delrin off-gassing (Spinei et al, 2021) and was filtered for total uncertainty <0.25 Dobson units (DU). A summary of this correction is provided in Section S3 in Supporting Information S1.…”
Section: Korea-united States Air Quality Studymentioning
confidence: 99%